Safety assessment of ancient buddhist pagoda induced by underpass metro tunnel blasting vibration. (March 2023) - Shi, Hanxu; Jiang, Nan; Zhou, Chuanbo; Zhnag, Yuqi; Yao, Yingkang; Zhou, Wenbin; Cai, Zhongwei
Highlights: Numerical simulation software was used to establish the numerical model of the ancient pagoda under the blasting load of the underpass tunnel. The maximum primary stress and vibration velocity were analyzed by numerical modeling in order to safeguard historic structures. The reason why the vibration velocity and stress of each part of irregular tower vary greatly is analyzed. The safety of the ancient pagoda is assessed according to the relevant norms. Abstract: In the blasting excavation project of the subway tunnel in the urban area, ensuring the safety of the surface buildings (structures) above the crossing area is the key concern. This paper is based on the blasting project of the ancient pagoda (Shengxiang Pagoda) under the tunnel between Pengliuyang Road Station and Simenkou Station of Wuhan Metro Line 5. To protect the integrity of the ancient buildings, this paper mainly adopts the numerical simulation method to analyze the dynamic response characteristics of the tower above the subway and realizes the safety assessment of the tower based on the maximum principal stress and vibration velocity control. The results show that the maximum error rate between the measured data and the numerical simulation results is only 11.9 %, which verifies the reliability of the numerical model and parameters. In the process of blasting vibration propagation, the vibration velocity of the tower body is affected by the whiplash effect and the elevation amplification effect. The vibration velocity of the tower bottom is 0.29 cm / s, and the vibration velocity of the tower tip reaches 4.29 cm / s. The vibration velocity of the upper part of the tower is much larger than that of the lower part. The stress distribution of the tower body is accompanied by stress concentration, with the maximum reaching 0.0442 MPa and the minimum only 0.014 MPa. The safety assessment of the ancient pagoda from the aspects of structural strength and vibration velocity can determine that the structure is safe under this condition. The research results are of great significance to the analysis of dynamic response characteristics and safety evaluation of ancient buildings under blasting load in urban complex environments.